Beta and Pilot Testing of the Surviving & Thriving Healthy Lifestyle App: A Countermeasure to Firefighters' Occupational Health Risks - Lidoriki, Irene; Anđelic, Bogdan; Lan, Fan Yun; Hershey, Maria Soledad; Georgakopoulos, Spyridon; Hadkhale, Kishor; Speros, Eleni; Sotos-Prieto, Mercedes; Christophi, Costas A.; Kales, Stefanos N. (My University, 2025)
Firefighters face elevated chronic disease risks, and interventions promoting healthier lifestyles are essential for improving their well-being. This study aimed to beta test and further evaluate a healthy lifestyle app (HLS app) for firefighters.
Keywords: firefighters; healthy lifestyle; nutrition; occupational risk; physical activity; resilience; sleep; smartphone application intervention